Co-production of knowledge for sustainability: an application of reflective practice in doctoral studies. Issue 2 (3rd March 2020) - Reed, Graeme; Dagli, Winifredo; Hambly Odame, Helen
ABSTRACT: This paper examines how doctoral students of sustainability science acquired reflective practice skills and engaged in critical reflection. Using the experience of a doctoral theory course on rural studies at the University of Guelph, students and faculty employed the principles of co-production and dialogue to explore the question: What does it mean to reflectively braid knowledge systems for sustainability? To do this, each doctoral scholar independently responded to the question, and then followed the response with an additional individual reflection. As a final discussion, we extended the reflection process and shifted the focus of conversation to ourselves and to the methodological aspects of the dialogical writing that we engaged in. Throughout this process, we used reflective practice and co-production to demonstrate how such processes must be integrated into the skills training and education of students who are taking inter- and trans-disciplinary programs. To finish, we reflect on the role of critical reflection, one that takes the normative dimensions of sustainability seriously, concluding that it is inseparable from reflective sustainability research and practice.